Mixed warty and sarcomatoid squamous cell carcinoma of vulva: a rare occurrence - Maharjan, Sailuja; Shahi, Arun; Satyal, Bandana; Baidya, Reena; Batajoo, Rajesh (Journal of Patan Academy of Health Sciences, 2022)
Vulvar cancer is a rare tumor accounting for